2015
DOI: 10.1089/cell.2014.0093
|View full text |Cite
|
Sign up to set email alerts
|

Timing Factors Affecting Blastocyst Development in Equine Somatic Cell Nuclear Transfer

Abstract: In nuclear transfer (NT), exposure of donor cell chromatin to the ooplast cytoplasm may aid reprogramming; however, the length of exposure feasible is limited by the developmental life span of the oocyte. We examined the effect of duration of nucleus-cytoplasmic exposure before activation and of in vitro maturation (IVM) in equine NT. In experiment 1, 24 h IVM and a delay of 2, 5, or 8 h between reconstruction and activation yielded 4%, 15%, and 11% blastocysts, respectively. In experiment 2, a 5-h activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In the horse, no differences in cleavage was reported after comparing 30 min and 2 h time windows between fusion to activation, in contrast to our findings [ 46 ]. However, Choi et al [ 15 ] have recently demonstrated that the use of horse oocytes immediately after reaching MII, combined with longer time periods (5- or 8-h) from reconstruction to activation, increased developmental competence after cloning. These results contrasts with those reported in the bovine, which determined that too prolonged exposure to arrested MII oocyte cytoplasm may result in a high incidence of structural abnormalities in nuclear material [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the horse, no differences in cleavage was reported after comparing 30 min and 2 h time windows between fusion to activation, in contrast to our findings [ 46 ]. However, Choi et al [ 15 ] have recently demonstrated that the use of horse oocytes immediately after reaching MII, combined with longer time periods (5- or 8-h) from reconstruction to activation, increased developmental competence after cloning. These results contrasts with those reported in the bovine, which determined that too prolonged exposure to arrested MII oocyte cytoplasm may result in a high incidence of structural abnormalities in nuclear material [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cloning to be successful, the differentiated state of the donor cell needs to be reset to an embryonic state within a relatively short period of time between embryo reconstruction and activation [ 11 , 12 ]. Some reports have focused on this step, which has demonstrated to be beneficial to epigenetic reprogramming and normal embryo development in different mammalian species [ 13 , 14 , 15 ]. However, when this interval was prolonged embryo development was compromised [ 16 , 17 , 18 ], probably due to oocyte aging [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic cells have been successfully isolated from frozen‐thawed equine semen (Brom‐de‐Luna, Canesin, Wright, & Hinrichs, ) but cloning was not attempted. Cloned foals have been produced from oocytes recovered from immature follicles by TVA (Choi, Velez, Macias‐Garcia, & Hinrichs, ; Choi et al., ) including production of a mitochondrial‐identical cloned foal via recovery of oocytes from two mares maternally related to the donor horse. Currently, few breed registries allow registration of cloned horses, however, many competitions that do not require strict breed registry allow cloned horses to compete, including the Fédération Equestre Internationale (FEI), which oversees equestrian competitions worldwide, including the Olympics.…”
Section: Cloning (Nuclear Transfer)mentioning
confidence: 99%
“…Until now, healthy foals were born only by using fetal and adult fibroblasts as nuclear donors, 5 , 16 , 29 32 with high rates of embryonic losses and postnatal mortality as typical outcomes, though. The most common defects observed in cloned foals included limb deformities, umbilical abnormalities and failure of passive transfer, 16 , 31 , 33 35 probably due to inefficient reprogramming of the donor cell.…”
Section: Introductionmentioning
confidence: 99%